Digital transformation and blockchain: Understanding the potential value and developing an adoption framework for APAC businesses - Nahood Pichay, Ahmad Faizal (2024)
The worldwide business community, including those in the Asia-Pacific (APAC) region, has widely adopted digital transformation. One of the significant catalysts for this shift is blockchain technology. This research serves to offer a comprehensive understanding of how blockchain can enhance digital transformations and suggests an adoption model suitable for businesses within APAC. Initially, the report offers definitions of both digital transformation and blockchain technology. It then delves into exploring how beneficial blockchain can be when applied to digital transformations by enhancing transparency, bolstering security measures, and improving overall efficiency levels. The research also addresses potential hindrances that organizations may encounter during their journey towards adopting this innovative tech solution like regulatory ambiguity or insufficient technical know-how. To establish a practical framework for APAC enterprises keen on incorporating it into their operations, the research outlines a five-stage procedure: Firstly identifying what business issues could benefit from employing blockchain; Secondly assessing if applying such advanced technology would indeed resolve the said issue effectively; Thirdly crafting an appropriate solution using Blockchain tailored specifically according to each enterprise's needs; Fourthly putting that plan into action followed by lastly keeping track of its performance while making necessary adjustments along the way as needed.